Earthquake Signature Detection Using Cubesat Technology - Nayyar, Shivang; Kumar, Sandeep; Suhag, Vikas (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
Cubesats play a vital role in development of new micro components being used in various micro/nano satellites. Cubesats have an effective small design and have the ability to get modified easily. Quakesat, a satellite being deployed by Space Systems Development Laboratory (SSDL) is used to study, detect, record, and downlink extremely low frequency (ELF) magnetic signals, which are used to predict earthquake activity. Quakesat is a live example of cubesat technology, uses non space application components and provides a low cost alternative to launch space missions and support nano satellite infrastructure in future.